Pre-treatment of p-coumaric acid reduced chilling injury by increasing some antioxidant and enzyme activity in loquat fruit to maintain post-harvest quality - Huifen Zhang; Yunting Xu; Jing Pu; Miao Wang; Jie Niu; Hongxia Wang; Xiaofu Tang; Ying Du; Xian Luo; Xiaoai Zhang; Yongqing Wang; Qunxian Deng (BMC Plant Biology)
Abstract Background Loquat (Eriobotrya japonica Lindl.) fruits are popular for their distinctive flavor and numerous health benefits. However, their short shelf life limits commercial viability. In this study, we sought to evaluate the effect of p-coumaric acid (p-CA) treatment at a concentration of 300 mg·L−1 on the quality of loquat fruits during storage. Results The results indicated that the p-CA treatment reduced fruit chilling injury, prevented fruit rot, and retarded the decomposition of soluble sugar, titratable acid, and phenolic substances. It also reduced accumulation of malondialdehyde, lignin, and other substances to maintain fruit quality. Additionally, p-CA treatment improved antioxidant activity of the fruit by promoting the synthesis of enzymatic antioxidants and activities of antioxidant enzymes. Conclusions In summary, p-CA application preserved the quality and enhanced the antioxidant capacity of post-harvest loquat fruits. Graphical Abstract